Comparison between the Use of LMA™ and SLIPA™ in Patients Undergoing Minor Surgeries. - Abd Rahman I,; Nurlia Y,; Wan Rahiza WM,; Esa K,; Nadia MN,; Raha AR, (Department of Surgery, UKM Medical Centre, 2012)
Supraglottic airway devices have been used as safe alternatives to endotracheal intubation in appropriate types of surgery. This was a prospective, randomised, single blind study comparing the use of LMA™ and SLIPA™ in terms of ease of insertion, haemodynamic changes and occurrence of adverse effects (e.g. blood stains on the device upon removal and sore throat). A total of 62 ASA I or II patients, aged between 18 to 70 years were recruited for this study. Patients were randomised into two groups; LMA™ and SLIPA™ group. Following induction of anaesthesia, an appropriate sized LMA™ or SLIPA™ was inserted after ensuring adequate depth of anaesthesia. Anaesthesia was maintained with oxygen, nitrous oxide and sevoflurane. The ease of insertion was graded and haemodynamic changes were recorded at 2 minute intervals up to 10 minutes after insertion of the airway devices. The presence of blood stains upon airway device removal at the end of surgery and incidence of sore throat was also recorded. No difficult insertion was experienced in either of these devices. Insertion was either easy [LMA™ 87.1% versus SLIPA™ 80.6% (p = 0.49)] or moderate [LMA™ 12.9% versus SLIPA™ 19.4% (p = 0.16)]. Throughout the study period, the haemodynamic changes that occurred in both groups were not statistically different. Traces of blood were noted on the surface of the device in 9.7% of patients in the SLIPA™ group versus 6.5% of patients in the LMA™ group. The incidence of sore throat was recorded in 12.9% versus 19.4% of patients in the SLIPA™ and the LMA™ groups respectively. These findings were not statistically significant. In conclusion, this study showed no significant differences between the use of LMA™ and SLIPA™ in terms of ease of insertion, haemodynamic changes and adverse effects in patients undergoing minor surgical procedures.